2018
DOI: 10.1007/s10517-018-4142-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Galectins-1 and Galectin-3 in Stomach and Colorectal Cancer with Tissue Eosinophilia

Abstract: We analyzed the expression of galectin-1 and galectin-3 in tumor tissue in stomach and colorectal cancer with and without tissue eosinophilia. Low expression of galectin-3 was detected in all patients with malignant gastrointestinal tumors irrespective of the presence of eosinophilia. Low expression of galectin-1 was detected only in patients with gastrointestinal cancer associated with eosinophilia. Association of galectin-1 expression with eosinophilic infiltration of the tumor tissue in stomach and colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Our study showed that blocking GAL-3 with antibodies ( Figure 5 ) reduced the pro-angiogenic ability of HUVECs and downregulated GAL-3 downstream target molecules, including VEGFR2 and JAG-1. Moreover, low expression of GAL-3 is a favorable prognostic factor in stomach and colorectal cancer [ 41 ]. We thus reasoned that BAP31 modulates angiogenesis by influencing the pVHL/HIF-1α axis, which up-regulates the expression of GAL-3 and, consequently, increases secreted GAL-3 and VEGFA and the promotion of angiogenesis by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that blocking GAL-3 with antibodies ( Figure 5 ) reduced the pro-angiogenic ability of HUVECs and downregulated GAL-3 downstream target molecules, including VEGFR2 and JAG-1. Moreover, low expression of GAL-3 is a favorable prognostic factor in stomach and colorectal cancer [ 41 ]. We thus reasoned that BAP31 modulates angiogenesis by influencing the pVHL/HIF-1α axis, which up-regulates the expression of GAL-3 and, consequently, increases secreted GAL-3 and VEGFA and the promotion of angiogenesis by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some biochemical studies for AML and control. and Malignancies) 17 . Through search in articles, we found similar results were matched with our results 18,19 .…”
Section: Discussionmentioning
confidence: 99%